Performance analysis in sport: Contributions from a joint analysis of athletes` experience and biomechanical indicators - Seve, C.; Nordez, A.; Poizat, G.; Saury, J. (Scandinavian Journal of Medicine & Science in Sports, 2013)
The purpose of this study was to test the usefulness of combining two types of analysis to investigate sports performance with the aim of optimizing it. These two types of analysis correspond to two levels of athletes` activity: (a) their experiences during performance and (b) the biomechanical characteristics of their movements. Rowing served as an illustration, and the activity of one female crew member was studied during a race. Three types of data were collected: (a) audiovisual data recorded during the race; (b) verbalization data obtained in interviews conducted afterward; and (c) biomechanical data. The courses of experience of the two rowers during the race were reconstructed on the basis of the audiovisual and verbalization data. This paper presents a detailed analysis of a single phenomenon of the race experienced by one of the rowers. According to the coaches, it reflected a dysfunction in crew coordination. The aim of this analysis was to identify the biomechanical characteristics of the rowers` movements that might explain it. The results showed that the phenomenon could be explained principally by an amplitude differential between the two rowers` strokes. On this basis, the coaches defined new training objectives to remedy the dysfunction in crew coordination.